Is There Association between Vitamin D Concentrations and Body Mass Index Variation in Women Submitted to Y-Roux Surgery? - Maria Tereza A. dos Santos; Fabiola Isabel Suano-Souza; Fernando Luiz Affonso Fonseca; Marise Lazaretti-Castro; Roseli Oselka Saccardo Sarni (Hindawi Limited, 2018)
Objective. To evaluate vitamin D deficiency and body composition of women submitted to bariatric surgery and relate their body mass index variation after surgery to 25(OH)D concentrations. Method. A cross-sectional and controlled study was performed including 49 obese adult volunteer women, submitted to Roux-en-Y gastric bypass (RYGB group). Collected Data. Body mass index (BMI), self-declared ethnicity, economic condition, physical activity level, serum concentrations of 25-hydroxycholecalciferol (25(OH)D; radioimmunoassay), parathormone, and body composition by dual-energy X-ray absorptiometry (Hologic DXA-QDR-1000) were collected. Results. 25(OH)D deficiency was found in 27 (55.1%) and 8 (21.1%) in the RYGB and control groups (p=0.002). Secondary hyperparathyroidism was more frequent in the RYGB group compared to the control group (15 (30.6%) versus 1 (2.6%); p=0.001). There was no relation of the studied variables and body composition with 25(OH)D deficiency. 25(OH)D concentrations were correlated (r=−0.531; p<0.001) with BMI reduction, regardless of vitamin D supplementation. Conclusion. Women submitted to bariatric surgery (RYGB) around three years ago had higher BMI and vitamin D deficiency, along with hyperparathyroidism, compared to the control group. There was no association between variables related to body composition and 25(OH)D concentrations. On the other hand, vitamin concentrations correlated negatively to BMI variation after undergoing surgery.